ANALISIS FAKTOR FUNDAMENTAL DAN RISIKO SISTEMATIK TERHADAP HARGA SAHAM PROPERTI DI BURSA EFEK INDONESIA - Retno Wardaningrum, 07.250.20009; Sudiyatno, Bambang (Students Journal of Economic and Management, 2012)
The purpose of this study is to test and analyze the effect of Return On Assets (ROA), Return on Equity (ROE), Price to Book Value (PBV), Debt to Equity Ratio (DER), and Systematic Risk (Beta) on stock prices of property companies in IDX. Population and sample are all listed property companies in Indonesia Stock Exchange (BEI) from the year 2005 to 2009, with sampling using purposive sampling method obtained by 75 data. The analysis was performed by multiple linear regression method. The results showed that the Return On Assets (ROA) has no effect on stock prices of property companies on the Stock Exchange. Return On Equity (ROE) has no effect on stock prices of property companies on the Stock Exchange. Price to Book Value (PBV) has positive effect on stock prices of property companies on the Stock Exchange. Debt to Equity Ratio (DER) has no effect on stock prices of property companies on the Stock Exchange. Systematic risk (beta) has no effect on stock prices of property companies on the Stock Exchange. Key words : Return On Assets (ROA), Return On Equity (ROE), Price to Book Value (PBV), Debt to Equity Ratio (DER), systematic risk and stock prices